Battling with the unwilling learner: a case for Gweru urban schools in Zimbabwe. - Mutemeri, Judith; Gudyanga, Anna (2016)
Observation of students in the learning situation has revealed that some students are unwilling learners, as becomes apparent in their loss of interest that is evidenced by absenteeism, low performance, non-submission of assignments, unruly behaviour, truancy, uncooperative behaviour and other negative behaviour. It would appear that among other many probable causes, classroom work makes very limited demands on the vast abilities students have (Holt, 1974). This is one of the reasons that account for students' failure at school. Based on the above observation, a case study was carried out in Gweru urban schools in Zimbabwe to find out from the educators and students what the underlying causes of uncooperative behaviour are. The study used both qualitative and quantitative research. A questionnaire and interviews were used as tools to collect data from teachers and students.A voice recorder was used to maintain an uninterrupted flow of interaction during interviews. Results revealed a heightening of negative attitude towards school from early childhood classes to secondary school classes. The implication of the findings for policy and practice are discussed in this article.